2020
DOI: 10.3390/polym12020334
|View full text |Cite
|
Sign up to set email alerts
|

New Materials for 3D-Printing Based on Polycaprolactone with Gum Rosin and Beeswax as Additives

Abstract: In this work, different materials for three-dimensional (3D)-printing were studied, which based on polycaprolactone with two natural additives, gum rosin, and beeswax. During the 3D-printing process, the bed and extrusion temperatures of each formulation were established. After, the obtained materials were characterized by mechanical, thermal, and structural properties. The results showed that the formulation with containing polycaprolactone with a mixture of gum rosin and beeswax as additive behaved better du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
45
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 58 publications
(107 reference statements)
9
45
0
2
Order By: Relevance
“…GR act as a plasticiser as it increased neat TPS elongation at break in 43%. The plasticising effect of gum rosin has been already observed for other bioplastics such as PLA [44], PCL [45] and Mater-Bi ® NF 866 [5]. Meanwhile, the other gum rosin derivatives produce no significant effect on the elongation at break of neat TPS (Figure 3c, p > 0.05).…”
Section: Resultsmentioning
confidence: 58%
“…GR act as a plasticiser as it increased neat TPS elongation at break in 43%. The plasticising effect of gum rosin has been already observed for other bioplastics such as PLA [44], PCL [45] and Mater-Bi ® NF 866 [5]. Meanwhile, the other gum rosin derivatives produce no significant effect on the elongation at break of neat TPS (Figure 3c, p > 0.05).…”
Section: Resultsmentioning
confidence: 58%
“…Finally, in Figure 12, it can be clearly observed how the craters and granules formed by the PEGR resin do not generate good cohesion in the polymer matrix, which confirms the saturation of the resin in the PLA. [26] 4 | CONCLUSIONS The present study has allowed to evaluate the effect of incorporating GR and PEGR into PLA polymeric matrix in contents of 5, 10, and 15 phr. Obtained results reveals a lubricating effect over PLA polymeric chains by the minimum content of GR and PEGR added (5 phr), obtaining greater processability of the formulations.…”
Section: Mechanical Propertiesmentioning
confidence: 93%
“…Natural resin from pine trees (gum rosin-GR) and derivatives are part of the renewable resources use as modifier agents in the development of biobased polymers for industrial applications. [25,26] GR is a natural resin extracted by exudation of the pine trees. [27] It consists in a complex mixture of terpenes, neutral components, and resin acids, mostly abietic acid (15-20%).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, pentaerythritol alcohol is used to stabilize gum rosin to increase its thermal resistance [30,35]. Gum rosin and its derivatives are fragile and rigid due to their hydrogenated phenanthrene ring structure [36,37]. Therefore, they have been used as environmental friendly additives in both thermoplastics and thermosets [30,[38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Aldas et al (2019) have studied the effect of gum rosin and gum rosin esters in a commercial thermoplastic starch-based polymeric matrix based on Mater-Bi ® -type bioplastic and found that gum rosin plasticized the polymeric matrix and that rosin esters acted as compatibilizers, enhancing the toughness of the Mater-Bi ® polymeric matrix [30,35]. Pavon et al (2020) studied the addition of raw gum rosin in PCL and found that gum rosin plasticizes the PCL matrix and improved its thermal stability [37]. analysed the effect of different gum rosin derivatives (gum rosin modified with maleic anhydride, disproportionated gum rosin, and two gum rosin esters) on a pure TPS matrix and concluded that the use of gum rosin and gum rosin derivatives not only stiffened the TPS polymeric matrix, but also ensure the thermal stability in the extrusion and injection moulding processes [28].…”
Section: Introductionmentioning
confidence: 99%